Influence of the mean period of ground motion on the inelastic dynamic response of single and multi degree of freedom systems. - Kumar, M. (Earthquake engineering & structural dynamics.)
This paper focuses on examining the effects of frequency content of the ground motion on the inelastic demands imposed on both single degree of freedom (SDF) and multi degree of freedom (MDF) steel-framed systems. A detailed literature review is conducted to identify the indicator that best represents the frequency content of ground motion. The mean period (Tm) of ground motion is selected owing to its ability to distinguish between various spectral shapes of ground motion, and its relationship with magnitude, distance and site characteristics. Inelastic displacement demands on SDF systems for target ductility levels are first studied in the light of Tm, using a suite of 128 ground motion records. The study is then extended to MDF systems with the help of incremental dynamic analysis by employing the same ground motion ensemble to assess the influence of Tm on various engineering demand parameters. The results obtained indicate that, for SDF systems, the amplification of displacements occurs when the period ratio between elastic period (Te) and Tm is lower than unity. For MDF systems, the results demonstrate that the influence of higher modes on the base shear and maximum storey drift profile becomes more pronounced, as Tm approaches the higher mode periods of the structure. These observations, for both SDF and MDF systems, tend to be more evident for higher levels of inelasticity. The significance of the results, with particular reference to European seismic design procedures, is highlighted.